2023
DOI: 10.18502/kme.v3i3.13505
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Exercise in Reducing Dysmenorrhoea Pain in Adolescent Women: A Literature Study

Lilis Setyowati,
Ollyvia Freeska Dwi Marta,
Nur Aini .
et al.

Abstract: This literature study aimed to identify the effectiveness of exercise in reducing pain thresholds in adolescents with dysmenorrhea. A literature search on Pubmed, Research Gate, ScienceDirect, and Proquest, was conducted from March to June 2022. Stretching, Zumba, FITT, Yoga, Aerobics, and Physical activity were the exercises found in the journal, and the study population was devoted to adolescents. The research design was a Randomized Controlled Trial (RCT) and Quasi-Experiment. The pain scale in the journal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Clinical trials have shown that engaging in aerobic exercise for 8 weeks can effectively reduce the severity of dysmenorrhea 14 . Several studies also support this finding 15–17 . However, Blakey et al found no correlation between physical activity and the incidence of dysmenorrhea 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have shown that engaging in aerobic exercise for 8 weeks can effectively reduce the severity of dysmenorrhea 14 . Several studies also support this finding 15–17 . However, Blakey et al found no correlation between physical activity and the incidence of dysmenorrhea 18 …”
Section: Introductionmentioning
confidence: 99%
“…14 Several studies also support this finding. [15][16][17] However, Blakey et al found no correlation between physical activity and the incidence of dysmenorrhea. 18 Several studies found a potential link between being overweight or obese and dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%